2009
DOI: 10.1007/s12094-009-0419-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of metastatic breast cancer

Abstract: Breast cancer is a heterogeneous disease characterised by a dysregulation of multiple pathways related to cell differentiation, cell cycle control, apoptosis, angiogenesis and development of metastasis. Acting against these pathways provides therapeutic targets for new targeted biologic therapies, which, in the future, might constitute a key for fighting cancer. The development of molecular technology in recent years has allowed a further comprehension of these mutations and dysregulated pathways leading to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Other examples of targeted enzyme therapy for cancer include the mammalian target of rapamycin inhibitors for breast and renal cell cancers (everolimus, temsirolimus) (2,55), the tyrosine kinase inhibitor regorafenib for colorectal cancer (33), and aromatase inhibitors, which decrease the production of estrogen and are used to treat estrogen receptor (ER)-positive breast cancer (61). Examples of monoclonal antibodies used to target a specific protein include bevacizumab, which targets vascular endothelial growth factor (VEGF), cetuximab and panitumumab, which bind epidermal growth factor receptor (EGFR) (colorectal cancer) (83), and trastuzamab, which targets human EGFR-2 and is used in HER-2 positive breast cancer (75).…”
Section: The Cancer Problemmentioning
confidence: 99%
“…Other examples of targeted enzyme therapy for cancer include the mammalian target of rapamycin inhibitors for breast and renal cell cancers (everolimus, temsirolimus) (2,55), the tyrosine kinase inhibitor regorafenib for colorectal cancer (33), and aromatase inhibitors, which decrease the production of estrogen and are used to treat estrogen receptor (ER)-positive breast cancer (61). Examples of monoclonal antibodies used to target a specific protein include bevacizumab, which targets vascular endothelial growth factor (VEGF), cetuximab and panitumumab, which bind epidermal growth factor receptor (EGFR) (colorectal cancer) (83), and trastuzamab, which targets human EGFR-2 and is used in HER-2 positive breast cancer (75).…”
Section: The Cancer Problemmentioning
confidence: 99%
“…Randomized phase III trials have already demonstrated significant clinical benefits of treatment with single-agent temsirolimus in advanced renal cell carcinoma and relapsed and/or refractory mantle cell lymphoma[91][93]. Phase I and II trials have also been carried out in other malignancies, such as glioblastoma[94], breast cancer[95], endometrial cancer[93], non-Hodgkin lymphomas[92], and multiple myeloma[93].…”
Section: Cancer Therapy and Targeted Autophagymentioning
confidence: 99%
“…Although tamoxifen did not directly simulate 18 F-FDG uptake in our in vitro experiments, the usefulness of metabolic flare seen on 18 F-FDG PET for indicating responsive tumors (7-9)-which may require tamoxifen action in an in vivo environment-is not invalidated. More recently, novel targeted agents that involve or directly target the PI3K-Akt pathway are emerging for the treatment of breast cancer (34). The success of such targeted therapies requires biomarkers of tumor response to guide individualized treatment decisions.…”
Section: Figurementioning
confidence: 99%